Digital Marketing Strategy Through Social Commerce to Increase Sales of MSME in Cimanggis Subdistrict, Depok City - Wulandari, Aghnia; Purnomo, Purnomo; Nadya Permata, Andhini; Puspa Anggraini, Leny; Aprilia, Tsaqif; Pebriyanti, Bunga; Dellya, Terryluana; Riandi, Ahmad; Hanafi, Fuad; Assyadera Marwan, Vannisa (STIE MBI, 2025)
UMKM are the backbone of the economy in many countries, contributing significantly to economic growth, job creation and poverty reduction. UMKM players need to adopt appropriate information technology to develop and compete in the digital era. However, many UMKM have difficulty choosing appropriate technology solutions due to limited expert staff and the large choice of technology products. Therefore, guidance in choosing technology that suits your type of business and needs is very important. The aim of this Community Development activity for UMKM is to provide training to UMKM in Cimanggis Subdistrict, Depok City. With a strategy that utilizes social media sites, it is hoped that UMKM players can develop more by collaborating with digital-based promotional and distribution media as an adaptation step to survive and transform into superior UMKM in the era of the industrial revolution 4.0. By utilizing digital marketing strategies through social commerce, there are social features and potential that are usually found on social media. So, competitive business in the current era really depends on the internet and individual experience in making strategies such as using the WhatsApp business application. This activity is carried out in the form of training by providing material and practicing the arrangement of strategic steps in using the WhatsApp business application. The target of this activity is UMKM in Cimanggis Sub-district, Depok City. The activity method used in this activity is the Descriptive method with an Experimental Learning approach, which is delivered through lectures, questions and answers, interactive discussions and practice. The result of this activity is an understanding in implementing strategies for using the WhatsApp business application and digital marketing strategies through social commerce to increase business sales, so that in the future it is hoped that UMKM players can strengthen their brand and be able to engage directly with customers, provide convenience for customers, increase sales and expand customer reach.